Use of the Reamer/Irrigator/Aspirator Decreases Carotid and Cranial Embolic Events in a Canine Model. (20th April 2016) - Miller, Anna N.; Deal, Dwight; Green, James; Houle, Timothy; Brown, William; Thore, Clara; Stump, David; Webb, Lawrence X.
Abstract : Background: Approximately 2 million patients in the United States annually undergo total joint arthroplasty with reaming and placement of intramedullary nails, resulting in extravasation of bone marrow and fat into the circulatory system and potentially causing fat embolism syndrome. Acute and chronic changes in mental status documented after these procedures may be related to embolic events. The Reamer/Irrigator/Aspirator (RIA) device has been shown to decrease intramedullary pressure during reaming. We hypothesized that the use of the RIA in a canine model would reduce the number of microemboli detected in the carotid artery and brain compared with nailing either with or without reaming. Methods: Twenty-four large canines underwent unreamed nailing (UR), sequentially reamed nailing (SR), or RIA-reamed nailing (RIA) of bilateral femora (eight dogs per group). During reaming and nailing, the number and size of microemboli transiting the carotid artery were recorded. After euthanasia, the brain was harvested for immunostaining and measurement of microinfarction volumes. Results: Total embolic load passing through the carotid artery was 0.049 cc (UR), 0.045 cc (SR), and 0.013 cc (RIA). The number and size of microemboli in the UR and SR groups were similar; however, the RIA group had significantly fewer larger-sized (>200-μm) emboli (p = 0.03). Pathologic examination of the brain confirmed particulate emboli, and histologic analyses demonstrated upregulation of stress-related proteins in all groups, with fewer emboli and less evidence of stress for RIA reaming. Conclusions: RIA reaming decreased microemboli compared with traditional reaming and unreamed nailing, suggesting that intramedullary pressure and heat are important variables. The documented embolic events and brain stress may help to explain subtle neurobehavioral symptoms commonly seen in patients after undergoing long-bone reaming procedures. Clinical Relevance: RIA reaming decreased cranial embolic events and may have an ameliorating effect on postoperative neurologic sequelae.